RETRACTED: Analysis Of Perceived Value Of Impulsive Buying With Attitudes And Beliefs As Mediator - Lily Purwianti; Keltine Richelle Chan (UNIVED Press, 2025)
RETRACTED NOTICE Following up on the review of articles published in the Ekombis Review Journal carefully, carefully, and considering the article entitled